Effect of wax crystal on the kinetic and morphology of gas hydrate deposition in water-in-oil emulsions. (15th December 2022) - Liu, Zhiming; Geng, Xin; Gao, Yan; Yao, Haiyuan; Chen, Haihong; Li, Zhigang; Song, Guangchun; Wang, Wuchang; Li, Yuxing
Highlights: The macro- and micro- morphologies of hydrate deposit layer were directly observed. Wax crystals altered the morphologies and growth pattern of hydrate deposit layer. A new method for measuring hydrate adhesive force under high pressure was developed. W/O emulsion with 1 wt% wax content showed the lowest adhesive force. Mechanisms for wax effect on the hydrate morphology and adhesion were proposed. Abstract: The deposition of hydrate and wax in the oil–gas pipelines are two of the flow assurance issues during the subsea oil production, they could reduce the cross-sectional area and increase the pressure drop, even the complete blockage could be caused by either of them in extreme conditions. Thus far, the study of the interaction between the hydrate and wax is still insufficient, especially in the process of the co-deposition of the two species. In this study, by utilizing the high-speed camera, the effect of wax content on the hydrate formation and deposition was explored, the macro- and micro- morphologies of the hydrate deposit layer in both the liquid and gas phase could be directly observed. It was found that with the increase of the wax content, the gas amount encapsulated in the hydrate increased first and then decrease in the tested wax content range. When hydrate was deposited on the wall, the morphologies of the deposit layer in the liquid phase and the growth pattern of the layer in the gas phase were altered by the presence of wax, the corresponding mechanisms were proposed based on the micro-behaviors of the hydrate layer. Finally, the adhesive forces of the hydrate formed in the emulsion with different wax content were measured by a self-developed method, the formed hydrate under 1 wt% wax content was discovered to show the lowest adhesive force when the deposition occurred. This work provides insights on the interaction of hydrate and wax in the W/O emulsion, and therefore could improve the flow-assurance strategies in the oil–gas production.